(untitled) (Conferencea, 2022)
The article gives information about contextual semantics of irony in the English language. Moreover, it approaches to the contextual semantics of irony from the semiotic point of view. And there are given some examples and situations from stories on this theme. The article contains definitions of some types of the irony.